Character Based Etnoducation: Cultural Intervention into the Character Education Program (Cultural Saturday) in Mataram, Indonesia - Faqih, M.; Mustakim, Mustakim; Najamuddin, Najamuddin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
The Cultural Saturday Program is an innovative effort to integrate local Sasak cultural values into character education in elementary schools in Mataram, Indonesia. This research evaluates the implementation, effectiveness and challenges of the program, while providing recommendations for future improvements. Using a qualitative descriptive approach, data was collected through interviews, observation and document analysis at SDN 43 Mataram and SD Hadi Sakti. The findings show that there is a structured program that is supported by a strong policy foundation and effective design, although there are challenges in the form of limited funding and minimal parental involvement. This program successfully instills values such as discipline, tolerance and social responsibility through culturally relevant activities. Recommendations include increasing financial support, increasing parental involvement, and utilizing digital technology to enrich cultural learning. This research contributes to discussions about culture-based education and its role in forming character holistically.